(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Alzheimer’s disease (AD) is the most common cause of dementia and is characterized by progressive cognitive decline. Early identification of AD is essential to stage the disease, assess risk, and prepare an advance care plan for the patient and family. This review discusses clinical and biological notions of “early” AD, and summarizes a stepwise diagnostic pathway: clinical evaluation, brief cognitive screening, functional assessment, exclusion of reversible causes, structural neuroimaging, and targeted use of biomarkers (CSF, PET, and blood-based markers). The recent expansion of blood-based biomarkers can make early diagnosis more accessible, but these tests must not be used as stand‑alone screening or diagnostic tools; results require interpretation within the clinical context.